Biodiversity responses to vegetation structure in a fragmented landscape: ant communities in a peri-urban coastal dune system - Cross, S.; Cross, A.; Merritt, D.; Dixon, Kingsley; Andersen, A. (Springer-Verlag, 2016)
© 2016 Springer International Publishing Switzerland. Habitat fragmentation often results in significant degradation of the structure and composition of remnant natural vegetation, leading to substantial biodiversity decline. Ants are an ecologically dominant faunal group known to be sensitive to vegetation degradation following fragmentation. We examined ant diversity and composition in relation to changes in vegetation structure in remnant coastal vegetation in the global biodiversity hotspot of southwestern Western Australia. The key features of vegetation structure driving the species and functional diversity and composition of ant communities were measures of cover of vegetation and bare ground. However, these effects were highly idiosyncratic at the species level. Cluster analyses based on plant species composition classified plots into two groups corresponding to relatively intact and degraded vegetation respectively. Although systematic changes in plant diversity and vegetation structure were observed between the two groups, key features from an ant perspective (native plant cover and bare ground) remained unchanged. Vegetation degradation consequently had little overall effect on ant species composition and functional diversity. The major disturbance–related impact on ant communities was through invasion by exotic ants, especially Pheidole megacephala; however, this occurred only in close proximity to development. Our results suggest that the priority for conserving ant diversity in our coastal dune system is the prevention of invasion by exotic species.